Relasi Makna dalam Pepatah-Petitih Minangkabau - M. Akbar Desril; Novia Juita (Persona: Kajian Bahasa dan Sastra, 2022)
The purpose of writing this article is to describe the types of meaning relations in Minangkabau proverbs. This type of research is a qualitative research using descriptive method. The subject of this research is speech or lingual unit of language that has a type of meaning relation. The object of this research is Minangkabau proverbs. The data will be analyzed with the following steps: (1) recording and translating the data in the data source into written language, namely from data from observations and documentation studies (2) identifying and classifying the types of meaning relationships (3) analyzing data in accordance with the research objectives and (4) formulating research findings. Based on the types of meaning relations in Minangkabau proverbs, there are four types of meaning relations analyzed, namely synonymy, antonym, hyponymy and meronymy. The types of synonymy meaning relations found as many as 51 expressions. The type of antonym meaning relation found 68 expressions. The type of hyponymy meaning relation found 24 expressions. The type of meronymy meaning relation found 63 expressions. The type of meaning relation that is often found is antonym type. Keywords: meaning relations, types, functions, proverbs